Virulence-encoding genes related to extraintestinal pathogenic E. coli and multidrug resistant pattern of strains isolated from neonatal calves with different severity scores of umbilical infections - Martins, Lorrayne de Souza A. [UNESP]; Motta, Rodrigo G.; Martinez, Antonio C.; Orsi, Henrique [UNESP]; Hernandes, Rodrigo T. [UNESP]; Rall, Vera L.M. [UNESP]; Pantoja, José C.F. [UNESP]; Nardi Júnior, Geraldo de; Ribeiro, Márcio G. [UNESP] (Elsevier, 2023)
Umbilical infections in calves comprise a major cause of neonatal mortality and have been related to a variety of microorganisms. E. coli is an opportunistic enteropathogen characterized by a diversity of virulence factors (VF). Nonetheless, the gene profiles that encode VF associated with umbilical infections in calves and their effect on the clinical severity remains unclear. In this scenario, microbial identification (with an emphasis on E. coli), was carried out among 150 neonatal calves (≤30 days of age) with umbilical infections, where the omphalopathies were clinically scored as mild, moderate, or severe. Also, a panel of 16 virulence-encoding genes related to extraintestinal pathogenic E. coli (ExPEC) were investigated, i.e., fimbriae/adhesins (sfa/focDEa, papA, papC, afaBC), toxins (hlyA, sat, cnf1, cdt), siderophores (iroN, irp2, iucD, ireA), invasins (ibeA), and serum resistance (ompT, traT, kpsMT II). Bacteria and yeasts isolates were identified using mass spectrometry. Bacteria, yeasts, and fungi were isolated in 94.7% (142/150) of neonatal calves sampled. E. coli was the agent most frequently isolated (59/150 = 39.3%), in pure culture (27/59 = 45.8%) and combined infections (32/59 = 54.2%), although a great variety (n = 83) of other species of microorganisms were identified. Clinical severity scores of 1, 2, and 3 were observed in 32.2% (19/59), 23.7% (14/59), and 44.1% (26/59) of E. coli infections, respectively. The ExPEC genes detected were related to serum resistance (traT, 42/59 = 72.2%; ompT, 35/59 = 59.3%, kpsMTII, 10/59 = 17%), invasins (ibeA, 11/59 = 18.6%), siderophores (iucD, 9/59 = 15.3%; iroN, 8/59 = 13.6%), and adhesins/fimbriae (papA, 8/59 = 13.6%; papC, 15/59 = 9.6%). The presence of each virulence gene was not associated with the case's clinical score. Among all isolates, 89.8% (53/59) showed in vitro resistance to sulfamethoxazole/trimethoprim and 59.3% to ampicillin (35/59), while 94.1% (55/59) revealed a multidrug resistant profile. Great complexity of bacteria, yeast, and fungi species was identified, reinforcing the umbilical infections of neonatal calves as a polymicrobial disorder. The high occurrence of E. coli (39.3%) highlights the role of this pathogen in the etiology of umbilical infections in calves. Furthermore, a panel of ExPEC genes was investigated for the first time among calves that were clinically scored for case severity. The high prevalence of traT and ompT indicates that these serum resistance-related genes could be used as biomarkers for further investigations of ExPEC isolates from umbilical infections. Our results contribute to the etiological investigation, clinical severity scoring, antimicrobial resistance pattern, and virulence-related to ExPEC genes involved in umbilical infections of neonatal calves.
Keywords: ExPEC genes; Infectious omphalopathies; MALDI-TOF MS; Neonatal calf